Scoping review to understand the potential for public health impacts of transitioning to lower carbon emission technologies and policies. (26th June 2020) - Tham, Rachel; Morgan, Geoff; Dharmage, Shyamali; Marks, Guy; Cowie, Christine
Abstract: Background : The transformation of the global energy sector from fossil-based fuels to low/non-carbon fuels will reduce environmental pollutant load, which in turn will benefit human health. However, with upscaling of emerging renewable technologies and energy sources, it is important to identify the potential for unintended health impacts, and to understand where the knowledge gaps lie with respect to health. We aimed to identify these gaps by conducting a scoping review. Methods : We conducted a systematic search of Medline, Web of Science, PubMed and EMBASE. We used broad search terms to capture literature associated with energy transitioning to low/non-carbon energy sources or related technologies, combined with terms relevant to measuring or estimating health outcomes/impacts associated with environmental exposures. We included original epidemiological studies, reviews, health impact assessments (HIAs), life cycle assessments (LCAs), and modelling studies that examined health impacts. Results : The search identified 6933 papers of which 81 original research and review papers were included in the review. The majority of studies were based on modelling scenarios. There were few papers reporting empirical epidemiological studies, either observational or interventional. The principal foci of the studies were: alternative energy scenario modelling; biofuels; wind energy; photovoltaic cells; transport; and building energy efficiency. Within those studies the depth and breadth of the health impact research was limited. Conclusions : There is a need to determine the potential for unintended health impacts that may arise from each energy transition scenario, as an adjunct to consideration of environmental and social impacts. Conducting LCAs or HIAs associated with current and emerging transitions, technologies, energy interventions, and policy decisions are likely to be the best methods, currently, for determining the potential for health impacts. Such research needs to be multidisciplinary and iterative to keep abreast of developments in new energy technologies, modelling methods and policy shifts in energy transitions.